Utilization of Leaflet Media on Mental Health to Increase Knowledge Among Pregnant Adolescents (International Forum of Researchers and Lecturers, 2025)
Mental health is a major aspect in determining the health of an individual. In 2019, out of every 8 people, or 970 million people worldwide lived with mental disorders. In 2020, the number of anxiety and depression disorders increased significantly. Preliminary estimates indicate an increase of 26% and 28% for anxiety disorders and major depression, respectively. Pregnant women are one of the vulnerable groups experiencing mental health problems, as women during pregnancy experience many physical, psychological, and emotional changes. In Indonesia, 28.7% of all pregnant women in Indonesia reported experiencing anxiety. Objective: To determine the effect of leaflet media on mental health on increasing the knowledge of pregnant adolescents. Research Methods: This study used quantitative methods through a pre-experimental approach with One Group Pretest-Posttest Design. Results: Based on the results of the study before education, most participants had a poor level of knowledge (80.0%), only 20.0% had sufficient knowledge. After education, the majority of pregnant women showed an increase in good knowledge (93.3%), while 6.7% had sufficient knowledge. Statistical tests showed a P-value of 0.000 < 0.05, indicating a significant difference between the pre-test and post-test. The negative Z-value also showed that the average pre-test score was lower than the post-test. Conclusion: The utilization of leaflet media is proven to have a significant positive effect in increasing the knowledge of pregnant adolescents.